Inconsistent Control Status of Office, Home, and Ambulatory Blood Pressure All Taken Using the Same Device: The HI–JAMP Study Baseline Data. (2nd September 2022) - Kario, Kazuomi; Hoshide, Satoshi; Tomitani, Naoko; Nishizawa, Masafumi; Yoshida, Tetsuro; Kabutoya, Tomoyuki; Fujiwara, Takeshi; Mizuno, Hiroyuki; Narita, Keisuke; Komori, Takahiro; Ogata, Yukiyo; Suzuki, Daisuke; et al.
Abstract: BACKGROUND: Inconsistencies between the office and out-of-office blood pressure (BP) values (described as white-coat hypertension or masked hypertension) may be attributable in part to differences in the BP monitoring devices used. METHODS: We studied consistency in the classification of BP control (well-controlled BP vs. uncontrolled BP) among office, home, and ambulatory BPs by using a validated "all-in-one" BP monitoring device. In the nationwide, general practitioner-based multicenter HI–JAMP study, 2, 322 hypertensive patients treated with antihypertensive drugs underwent office BP measurements and 24-hour ambulatory BP monitoring (ABPM), consecutively followed by 5-day home BP monitoring (HBPM), for a total of seven BP measurement days. RESULTS: Using the thresholds of the JSH2019 and ESC2018 guidelines, the patients with consistent classification of well-controlled status in the office (<140 mmHg) and home systolic BP (SBP) (<135 mmHg) ( n  = 970) also tended to have well-controlled 24-hour SBP (<130 mmHg) ( n  = 808, 83.3%). The patients with the consistent classification of uncontrolled status in office and home SBP (n  = 579) also tended to have uncontrolled 24-hour SBP ( n  = 444, 80.9%). Among the patients with inconsistent classifications of office and home BP control ( n  = 803), 46.1% had inconsistent ABPM-vs.-HBPM out-of-office BP control status. When the 2017 ACC/AHA thresholds were applied as an alternative, the results were essentially the same. CONCLUSIONS: The combined assessment of the office and home BP is useful in clinical practice. Especially for patients whose office BP classification and home BP classification conflict, the complementary clinical use of both HBPM and ABPM might be recommended. Graphical Abstract: